2013
DOI: 10.1021/jm3015603
|View full text |Cite
|
Sign up to set email alerts
|

Endowing Indole-Based Tubulin Inhibitors with an Anchor for Derivatization: Highly Potent 3-Substituted Indolephenstatins and Indoleisocombretastatins

Abstract: Colchicine site ligands with indole B rings are potent tubulin polymerization inhibitors. Structural modifications at the indole 3-position of 1-methyl-5-indolyl-based isocombretastatins (1,1-diarylethenes) and phenstatins endowed them with anchors for further derivatization and resulted in highly potent compounds. The substituted derivatives displayed potent cytotoxicity against several human cancer cell lines due to tubulin inhibition, as shown by cell cycle analysis, confocal microscopy, and tubulin polymer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
50
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(58 citation statements)
references
References 54 publications
6
50
1
Order By: Relevance
“…For the dimethylaminophenyl derivatives, any substituent ortho to the amine causes a drastic reduction in potency, irrespective of their electron donor or acceptor character, or of their hydrogen -bond donor or acceptor character or even to their different shape, such as for instance for amino, formyl, or cyano groups. These results are apparently at odds with our previous results on indole isocombretastatins [44], where the same substituents at the indole 3 position result in potent tubulin inhibitory and cytotoxic compounds.…”
Section: Structure Activity Relationships (Sar) Studycontrasting
confidence: 98%
See 1 more Smart Citation
“…For the dimethylaminophenyl derivatives, any substituent ortho to the amine causes a drastic reduction in potency, irrespective of their electron donor or acceptor character, or of their hydrogen -bond donor or acceptor character or even to their different shape, such as for instance for amino, formyl, or cyano groups. These results are apparently at odds with our previous results on indole isocombretastatins [44], where the same substituents at the indole 3 position result in potent tubulin inhibitory and cytotoxic compounds.…”
Section: Structure Activity Relationships (Sar) Studycontrasting
confidence: 98%
“…The sampling of small atomic fluctuations in macromolecules by molecular dynamics simulations can be used to find conformations relevant for binding not present in the experimentally determined structures [42,43]. We have previously shown that the application of molecular dynamics simulations can help in finding consistent binding modes for series of related ligands for which docking studies alone suggested inconsistent binding modes not supported by structure e activity relationships [10,44]. In doing so, we have shown that the tubulin zone 1 where the tropolone ring of colchicine or the benzodioxole ring of podophyllotoxin bind (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…[27][28][29] The introduction of different side chains around the indole nucleus has resulted in the development of various therapeutic drugs, including obatoclax, 30 and sunitinib, 31 as well as many lead compounds that boast a wide variety of biological activities. Modifying the 2 nd and 5 th positions of the indole moiety has been shown to be crucial for receptor binding and activation.…”
Section: Introductionmentioning
confidence: 99%
“…[12][13][14] Although COL has been shown to possess antitumor properties, 15,16 its therapeutic use is limited by toxicity problems; this has led to the consideration of analogs. [17][18][19] When COL binds to TU, it inhibits the assembly into microtubules and microtubule dynamics. 20 The binding process is slow and strongly temperature-dependent, 21 while dissociation is kinetically unfavorable due to its high activation energy.…”
Section: Introductionmentioning
confidence: 99%